2006
DOI: 10.1021/jm0611556
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Glycoside Inhibitors of Glioma and Melanoma Growth

Abstract: An N-acetylglucosaminide derivative with a pentaerythritol substituent at position C-6 was previously synthesized and shown to inhibit neural tumor growth. Now, we report the preparation of a series of new synthetic compounds introducing systematic changes in the nature, polarity, and size of the sugar substituents. The antimitotic activity of the new compounds was tested on cultured rat (C6) and human (U-373) glioma lines and on a human melanoma line (A-375). The antimitotic and antitumoral activity of the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 19 publications
1
54
0
Order By: Relevance
“…22 Interestingly, compound 1 is a glycoside of oleyl alcohol, and the presence of the oleyl group was the main structural difference with respect to the parent glycosides that resulted less inhibitory of glioma cell division than 1. 7 The treatment of C6 cells with oleic acid (100 µM) for 24 h afforded a 1 H NMR spectrum similar to that obtained with 1 (10 µM) (Figure 1c), in which the major metabolic change was also the intensity of the signal at 0.67 ppm. In this case, a 3-fold decrease in the peak intensity from CoA metabolites was observed.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…22 Interestingly, compound 1 is a glycoside of oleyl alcohol, and the presence of the oleyl group was the main structural difference with respect to the parent glycosides that resulted less inhibitory of glioma cell division than 1. 7 The treatment of C6 cells with oleic acid (100 µM) for 24 h afforded a 1 H NMR spectrum similar to that obtained with 1 (10 µM) (Figure 1c), in which the major metabolic change was also the intensity of the signal at 0.67 ppm. In this case, a 3-fold decrease in the peak intensity from CoA metabolites was observed.…”
Section: Resultssupporting
confidence: 52%
“…2 On the basis of structural elements of the natural inhibitor, we synthesized series of oligo-and monosaccharides, which were tested as inhibitors of brain tumor cell division. [3][4][5][6][7] Recently we have obtained a family of N-acyl-glucosamine derivatives, some of which showed antimitotic activity against rat C6 glioma cells with low IC 50 values. 7 The results obtained indicated that the activity was increased by a long hydrocarbon chain at position C-1 of the glucosamine backbone, the most inhibitory compound being the oleyl glycoside 1 (Chart 1).…”
Section: Introductionmentioning
confidence: 99%
“…Sulfoglycolipid IG20 seems to belong to this last group of compounds that exert neuroprotection through a mechanism that involves a given cellular signalling pathway. In line with this proposal are the various families of glycolipids and sulfoglycolipids synthesised at our laboratory that by acting on intracellular signalling pathways exhibit antimitotic activity in melanoma and glioma cells (Doncel-Perez et al, 2013;Garcia-Alvarez et al, 2007). In this line is IG20 that belongs to a new family of sulfoglycolipids that emerged in the context of the synthesis of new antineoplasic agents with potential therapeutic application in glioma and melanoma, and that promoted neuritic growth and myelination (Garcia-Alvarez et al, 2015).…”
Section: -Discussionmentioning
confidence: 78%
“…This last property mainly focused the treatment of cerebral gliomas (Doncel-Perez et al, 2013;FernandezMayoralas et al, 2003;Garcia-Alvarez et al, 2007). The synthetic strategy was inspired in the fact that in mammalian brain there are natural inhibitors of astroblasts and astrocytes division (Nieto-Sampedro, 1988;Nieto-Sampedro and Broderick, 1989); one such inhibitor is neurostatin, first found in the rat brain (Valle-Argos et al, 2010).…”
Section: -Introductionmentioning
confidence: 99%
See 1 more Smart Citation